2009
DOI: 10.4238/vol8-3gmr562
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the S65C mutation in the hemochromatosis gene in Brazil

Abstract: ABSTRACT. Development of hereditary hemochromatosis is associated with the C282Y, H63D or S65C mutations in the hemochromatosis gene. Though there is extensive knowledge about the former two, there is little information on the mechanism of action and the allelic frequency of the S65C mutation. We examined the prevalence of the S65C mutation of the hemochromatosis gene in Brazilians with clinical suspicion of hereditary hemochromatosis. Genotyping for this mutation was carried out in 633 individuals with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…Because no studies on this subject have been previously published in Minas Gerais, a contextual evaluation of our results is not yet possible. It is likely that S65C mutations in the HFE gene were not identified in our study due to the low frequency of this mutation and the limited number of patients analyzed [ 70 ]. The frequency of the H63D mutation was higher for both the case (35.4%) and control subjects (17.9%), as expected [ 5 , 59 , 61 – 62 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because no studies on this subject have been previously published in Minas Gerais, a contextual evaluation of our results is not yet possible. It is likely that S65C mutations in the HFE gene were not identified in our study due to the low frequency of this mutation and the limited number of patients analyzed [ 70 ]. The frequency of the H63D mutation was higher for both the case (35.4%) and control subjects (17.9%), as expected [ 5 , 59 , 61 – 62 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The H63D mutation is two or three times more frequent than C282Y mutation and the prevalence of heterozygous and homozygous for H63D mutation varies between 15 and 40% and 2.5 and 3.6%, respectively, and the frequency of C282Y/H63D genotype is approximately 2% (15,16). Regarding the S65C mutation, the frequency in Caucasians varies between 1% and 4% (9,10,18,19).…”
Section: Discussionmentioning
confidence: 98%
“…Besides, no other study in the same geographical region where our reserach was performed, has been reported. It is also worthy of note that, among the available studies, there is a disparity in the sample number and in the eligibility criteria ( Bittencourt et al, 2002 , 2009 ; Oliveira et al., 2009 ; Santos et al, 2011 ; Leão et al, 2014 ). As shown in Figure 4 , which compares different groups of genotypes, comorbidities such as alcoholism or other diseases that may affect iron metabolism do not exclude the diagnosis of HH.…”
Section: Discussionmentioning
confidence: 99%